Justice for Julian Assange. (Economist, 2019)
The article reports on the criminal prosecution of Julian Assange, co-founder of nonprofit WikiLeaks, due to hacking of U.S. Defense Department computers. Topics discussed include accusation against Assange for helping American activist and whistleblower Chelsea Manning try to crack the password to a classified military network, and actions that British courts should do with the U.S. request for the extradition of Assange.